The Management of Complicated Crown Fracture of Anterior Primary Teeth - Puji Kurnia (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2021)
Background: Injury in the primary teeth and their supporting structures is one of the most common dental health problems observed in children. Injuries in children occurred from an external forces which classified in to dental emergency treatment in pediatric growth and development. A child is perceived to be in a dynamic state of growth, both mentally and physically. Curiosity about surrounding environment and urging to explore may lead to dental injuries. A vital pulpectomy and continued selection of an appropriate restoration after a traumatic injury can mentain the primary tooth in its arch until the time of exfoliation. Purpose: Reported the management of complicated crown fractures in the upper left primary teeth. Case Report: This report presented a 2 years old boy with complicated crown fracture on the upper left primary teeth. The parents gave the history of trauma related to front region of the jaw and they wanted to restore the involved tooth without getting extraction. After an intra oral examinations, it was observed that crown was fracture with vital dental condition. Case Management: After removing the fractured fragment, a vital pulpectomy was conducted in three visit periods at the remaining upper left primary teeth with final glass ionomer cement restoration using strip crowns. Conclusion: The importance of reconstruction on anterior primary teeth after traumatic injury provides both functional and aesthetic restorations for the child, what reflects on masticatory efficiency, increased self-steam and also phonetic improvements.